Roles of IEC in supporting effective Smart City standards. Issue 1 (19th June 2019) - Mulquin, Michael J.
Abstract : The International Electrotechnical Commission is using its systems approach, honed in the development of international smart grid standards, to identify the requirements of cities and smart city solution providers for tried and tested solutions to common challenges and is working with the wider international standards development community to develop the coherent and interoperable packages of standards needed. This study discusses such developments and provides insights into the current state‐of‐the‐art.